2022
DOI: 10.3390/ijerph19052822
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Resilience and Life Satisfaction in the Relationship between Stress and Burnout in Medical Students during the COVID-19 Pandemic

Abstract: Following the WHO’s declaration of a public health emergency due to the COVID-19 outbreak, the subsequent quarantine and confinement measures that were adopted, including distance learning measures, were shown to have caused a significant deterioration in the mental health of medical students. The goal of this study was to explore the mediating role of resilience and life satisfaction in the relationship between perceived stress and burnout among medical students in the context of COVID-19. A transversal asses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…The aim of this study was to explore the indirect effects of resilience on indices of psychological well-being via role stress. The majority of research on resilience during the pandemic has investigated its mediating role in the association between stress and burnout, stress and quality of life and social isolation and wellbeing [ 64 66 ]. Furthermore, these studies on resilience have largely focused on frontline medical care workers with few studies investigating resilience among other population groups differentially impacted by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to explore the indirect effects of resilience on indices of psychological well-being via role stress. The majority of research on resilience during the pandemic has investigated its mediating role in the association between stress and burnout, stress and quality of life and social isolation and wellbeing [ 64 66 ]. Furthermore, these studies on resilience have largely focused on frontline medical care workers with few studies investigating resilience among other population groups differentially impacted by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature on the stress of medical students, resilience training is also regarded as an effective factor to relieve the impact of stress (88). Duarte et al (89) concluded that resilience played a mediating role in perceived stress and burnout (exhaustion) among medical students during the COVID-19 lockdown. Resilience is considered necessary for medical students to overcome the stress from academic and future employment and to achieve academic success (90).…”
Section: The Partial Mediating Role Of Resilience In Stress and Acade...mentioning
confidence: 99%
“…Perceived stress during the COVID-19 pandemic has been previously reported as high among medical students. Duarte et al, performed a transversal assessment of students attending a medical school in northern Portugal through an online survey, and PSS scored an average of 21, with a standard deviation of 7 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%